Extended behavioural device modelling and circuit simulation with Qucs-S. Issue 3 (4th March 2018) - Brinson, M. E.; Kuznetsov, V.
ABSTRACT: Current trends in circuit simulation suggest a growing interest in open source software that allows access to more than one simulation engine while simultaneously supporting schematic drawing tools, behavioural Verilog-A and XSPICE component modelling, and output data post-processing. This article introduces a number of new features recently implemented in the 'Quite universal circuit simulator – SPICE variant' (Qucs-S), including structure and fundamental schematic capture algorithms, at the same time highlighting their use in behavioural semiconductor device modelling. Particular importance is placed on the interaction between Qucs-S schematics, equation-defined devices, SPICE B behavioural sources and hardware description language (HDL) scripts. The multi-simulator version of Qucs is a freely available tool that offers extended modelling and simulation features compared to those provided by legacy circuit simulators. The performance of a number of Qucs-S modelling extensions are demonstrated with a GaN HEMT compact device model and data obtained from tests using the Qucs-S/Ngspice/Xyce Â © /SPICE OPUS multi-engine circuit simulator.